Implementing Green Logistics in Agricultural MSMEs in Sukabumi, West Java, Indonesia: Its Impact on Operational Efficiency and Environmental Sustainability - Nabila Eprilya Putri; Fitrina Lestari; Riyan Mirdan Faris (CAKRAWALA : Management Science Journal, 2025)
Green Logistics (GL) presents a strategic framework for enhancing operational efficiency and environmental sustainability two key imperatives in modern supply chains. However, its implementation among MSMEs, particularly in agriculture and in developing countries, remains both understudied and underutilized. This study explores the extent to which GL practices influence Operational Efficiency and Environmental Sustainability within agricultural MSMEs in Sukabumi, West Java, Indonesia. Adopting a mixed methods approach, quantitative data were collected from 76 MSME actors and analyzed using SEM PLS, while qualitative insights were gathered through open ended survey questions. Results show that GL significantly impacts Operational Efficiency (β = 0.593) and Environmental Sustainability (β = 0.485), with Efficiency acting as a partial mediator (β = 0.406). The R² values of 0.633 and 0.352 suggest strong predictive validity for the structural model. The qualitative data reinforce these findings by highlighting real world constraints limited access to eco-friendly tools, a lack of technical knowledge, and insufficient training. While geographically localized, the study provides transferable insights into the broader barriers and potential of GL adoption among MSMEs in emerging economies. It also affirms the relevance of the NRBV and GSCM frameworks when adapted to rural and resource constrained contexts.